Opinions and attitudes toward artificial intelligence among operating room nurses: a descriptive meta-analysis based on the comparative studies of the different opinions - Ye, Juhua; Huang, Junwu (Frontiers in Artificial Intelligence, 2025)
BackgroundArtificial intelligence (AI) is defined as the capability of machines to perform tasks that typically require human intelligence. Robots have major roles during surgeries as well as in the operating rooms (ORs). Therefore, it is expected for nurses working in ORs to be knowledgeable about those new technologies and the preparation of robots for surgeries. In this analysis, we aimed to represent the opinions and attitudes of ORs nurses toward AI.MethodsOnline databases were searched for relevant publications. AI based questions were asked to the ORs nurses and the percentage of participants who agreed or disagreed to specific questions were recorded. The RevMan application was used to carry out statistical analysis, whereby odds ratios (OR) and 95% confidence intervals (CI) were used to represent the results.ResultsSix studies consisting of a total number of 1,197 participants were included. ORs nurses believe that AI and robotic nursing applications will significantly reduce the workload of nurses with OR: 75.73, 95% CI: 8.28–692.86; p = 0.0001. In addition, a majority of ORs nurses significantly accepted the application of AI in nursing (OR: 63.70, 95% CI: 2.15–1890.57; p = 0.02) and significantly believed that AI will revolutionize in the field of nursing (OR: 15.27, 95% CI: 3.47–67.15; p = 0.0003). In addition, they significantly agreed that robotic technologies are very important (OR: 12.57, 95% CI: 6.44–24.54; p = 0.00001). The ORs nurses significantly disagreed to the fact that robotic technologies are too expensive and unnecessary (OR: 0.02, 95% CI: 0.01–0.04; p = 0.00001). Nevertheless, even though majority of the ORs nurses agree that robotic checking system is time consuming, the result was not significant (OR: 1.38, 95% CI: 0.79–2.40; p = 0.26).ConclusionMajority of the nurses believe that AI and robotic nursing applications will significantly reduce the workload of nurses, they believe that AI will significantly revolutionize in the field of nursing, and they believe that robotic technologies are very important. However, due to the several limitations from this analysis, the results should be considered with caution.